Comparison of the efficacy of an education program for people with diabetes and insulin pump treatment (INPUT) in a randomized controlled trial setting and the effectiveness in a routine care setting: Results of a comparative effectiveness study. Issue 10 (October 2019) - Bergis, Dominik; Ehrmann, Dominic; Albrecht, Carmen; Haak, Thomas; Kulzer, Bernhard; Hermanns, Norbert
Highlights: Education with the INPUT program is effective under conditions of routine care. Reduction of HbA1c in the IT was significantly greater than in the RCT. Improvement of hypoglycemia- and psychosocial problems was equal in both trials. Patients with higher HbA1c levels were most likely to benefit from INPUT. Abstract: Objective: To compare the efficacy of an education program for people with diabetes and insulin pump treatment (INPUT) in a randomized controlled trial (RCT) to the effectiveness in an implementation trial (IT). Methods: 135 people with diabetes on insulin pump treatment (CSII) underwent structured education with INPUT under RCT-conditions, 191 people with diabetes on CSII underwent structured education with INPUT under IT-conditions. Baseline characteristics and treatment outcomes at the 6-month follow-up were compared. Results: At baseline, RCT-participants were younger (42.7 ± 14.2 vs. 47.2 ± 14.1 years, p = 0.005), had higher HbA1c-values (8.3 ± 0.8% vs. 7.8 ± 1.2%, p = 0.001) and had more diabetes-related distress (27.8 ± 16.4 vs 22.4 ± 14.4, p = 0.002). At follow-up, INPUT results were comparable under the RCT and IT settings. After adjustment for baseline HbA1c, reduction of HbA1c in the IT was significantly greater than in the RCT (Δ0.17%; 95% CI 0.023–0.319%, p = 0.024). Participants with higher HbA1c-levels, more diabetes-related distress and more hypoglycemia problems were most likely to benefit from INPUT regardless of the trial setting. Conclusions: Efficacy of the INPUT program for people with CSII was demonstrated under RCT- and routine care conditions. Practice implications: Education with the INPUT program is effective not only under standardized RCT conditions but also under conditions of routine care.